2022
DOI: 10.3390/jcm11112963
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy and Safety of Brigatinib in First-Line Treatments for Patients with Anaplastic Lymphoma Kinase-Positive Non-Small-Cell Lung Cancer: A Systematic Review and Indirect Treatment Comparison

Abstract: (1) Background: The relative efficacy and safety of brigatinib compared with other next-generation anaplastic lymphoma kinase (ALK) inhibitors remains unclear, as first-line head-to-head trials have not been conducted. (2) Methods: Electronic databases were systematically searched for eligible randomized controlled trials (RCT) from January 2010 to October 2021. Outcomes evaluated by indirect treatment comparison (ITC) included progression-free survival (PFS), overall survival (OS), objective response rate (OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Both studies demonstrated that brigatinib and alectinib had a comparable performance but authors emphasized the importance of performing a direct comparison via a randomized controlled study [ 19 , 20 ]. Further, Yu et al [ 21 ] preformed an indirect comparison by reviewing ALEX, J-ALEX, ALESIA, and ALTA-1L studies and found that brigatinib was superior to other ALK inhibitors like crizotinib and ceritinib, and its efficacy and safety profile had comparable performance when compared to second-generation ALK inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies demonstrated that brigatinib and alectinib had a comparable performance but authors emphasized the importance of performing a direct comparison via a randomized controlled study [ 19 , 20 ]. Further, Yu et al [ 21 ] preformed an indirect comparison by reviewing ALEX, J-ALEX, ALESIA, and ALTA-1L studies and found that brigatinib was superior to other ALK inhibitors like crizotinib and ceritinib, and its efficacy and safety profile had comparable performance when compared to second-generation ALK inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the long history of CNS disease, we decided to opt for this molecule, a second generation ALK inhibitor, instead of crizotinib, for its ability to penetrate through the blood-brain barrier, and its higher efficacy and lower risk of emerging resistance [14,37,38]. While there are no data on the use of brigatinib in pediatric ALK-positive tumours such as ALCL, IMT, neuroblastoma and glioma, data in adults affected by NSCLC showed superiority of brigatinib compared with crizotinib in terms of progression-free survival, response rate, intracranial tumor response rate, and death rate [37][38][39][40]. Given the refractoriness history of this patient and the difficulty to achieve clinical and molecular remission, we also decided to administer brigatinib for additional 12 months after allogeneic HSCT to prevent relapse.…”
Section: The Role Of Alk Inhibitors In the Treatment Of Patients With...mentioning
confidence: 99%
“…Ethical considerations may also make a direct comparison impossible, as is often the case when developing treatments for life-threatening diseases. Moreover, direct comparison can be infeasible, such as for rare diseases where patient numbers can be very low [ 4 , 5 , 6 ]. Finally, if multiple comparators are of relevance to a particular indication, an RCT directly comparing all comparators of interest may be impractical.…”
Section: Introductionmentioning
confidence: 99%